Beyond experimentation. Online strategies in social services - Sandra Beelen; Katrien Van den Meerschaute (Journal of Social Intervention: Theory and Practice, 2010)
Beyond experimentation. Online strategies in social services Young people in Flanders spend considerable amounts of time online and an increasing number of welfare services are exploring the opportunities of social media for reaching their target groups. Accessible and high-quality youth welfare services are crucial in the battle against exclusion. This practice-based paper aims to take a closer look at the challenge of accessibility that welfare services face. By illustrating developments in the JACs, Flanders’ leading youth welfare centers, we will describe how ICT is used as a strategy to combat barriers and increase access for youngsters and in particular for those hard to reach. We conclude by making a call for further research to evaluate the effects of ICT in social work in order to inspire, nourish and innovate social work practice.